Dysfunction of mitochondria and GABAergic interneurons in the anterior cingulate cortex of individuals with schizophrenia. (December 2022) - Kondo, Mari A.; Norris, Alexis L.; Yang, Kun; Cheshire, Madeline; Newkirk, Isabelle; Chen, Xiangning; Ishizuka, Koko; Jaffe, Andrew E.; Sawa, Akira; Pevsner, Jonathan
Abstract: Here we re-analyze RNA-sequencing data from the anterior cingulate cortex (ACC) of SZ patients using recent methods to improve accuracy and sensitivity of results, such as the quality surrogate variable analysis (qSVA) method and the derfinder R package. We found that genes significantly down-regulated in SZ demonstrated an enrichment for parvalbumin-positive interneurons (FDR < 0.0001). Down-regulated genes were also enriched in oxidative phosphorylation functions (FDR < 0.05). We also addressed whether lifetime exposure to antipsychotics might influence gene expression, highlighting DUSP6, LBH, and NR1D1 . Our results support the role of redox imbalance/mitochondrial dysfunction and implicate interneuron subtypes in SZ pathophysiology. Highlights: Gene expression in anterior cingulate cortex shows molecular changes in schizophrenia. Down-regulated gene expression enriched in parvalbumin-positive interneurons. Down-regulated gene expression also enriched in oxidative phosphorylation functions. Supportive evidence for role of redox imbalance and mitochondrial dysfunction in SZ.